(untitled) (Research, Society and Development, 2021)
A systematic review of the literature was carried out with the aim of determining whether sleep-wake cycle disorders can be considered markers of suicidal ideation. To carry out the review and answer the research question, a search was conducted in the bibliographic databases of the health area: Medline, Scielo and LILACS during the months of may to december 2020. Original quantitative studies and qualitative reviews were included, as well as meta-analyses, published in the last 10 years in Spanish, English and Portuguese. Thirty-nine articles were found that met the inclusion criteria, of which 37 were written in English and 2 in Portuguese. The Medline database contributed 79.4 % of the articles used. Of the articles, 87.1% corresponded to original quantitative studies. The present systematic review showed that sleep disorders are an independent risk factor for suicidal behavior in different clinical contexts and socio-cultural settings.